Tenpin Bowling UMP women’s team won gold medal in 2023 East Coast IPT Tenpin Bowling Championship Series 3 - Nor Salwana, Mohammad Idris (UMPSA, 2023)
TUNJONG, 13 July 2023 - The Tenpin Bowling Universiti Malaysia Pahang (UMP) women’s team won a gold medal in the group category and won medals in each category at the 2023 East Coast IPT Tenpin Bowling tournament at Lite Superbowl JB7, Tunjong, Kelantan recently.